2022
DOI: 10.21203/rs.3.rs-1668736/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insufficient weight gain under 3 years is associated with short stature in school-aged children

Abstract: Purpose: If children show inadequate infant weight gain, their growth velocity will also decrease, especially £3 years of age. We hypothesized that such children may not only lead to being underweight but also short stature during childhood, and this trend will follow them through adolescence. Methods: A total of 271 children were enrolled. The Pearson correlation coefficients were calculated to determine the relationships of the increment of weight gain £3 years, from birth to 1.6 years and from 1.6 years to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The short stature among the Rohingya women can be constitutional or may be a reflection of chronic food insecurity during childhood (Schmeer & Piperata, 2017 ; Weigel et al, 2016 ). Prior works revealed that insufficient weight gain during early childhood correlates with shorter height in later life (Koyama et al, 2022 ). Short stature may lead to complications during pregnancy (Sohlberg et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The short stature among the Rohingya women can be constitutional or may be a reflection of chronic food insecurity during childhood (Schmeer & Piperata, 2017 ; Weigel et al, 2016 ). Prior works revealed that insufficient weight gain during early childhood correlates with shorter height in later life (Koyama et al, 2022 ). Short stature may lead to complications during pregnancy (Sohlberg et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%